Pokémon. Sun & Moon. 2 - Kusaka, Hidenori; Turnage, Bryant (VIZ Media, LLC, 2018)
Sun and Moon participate in the Full Power Tournament to win the island challenge amulet, but Sun has to deal with the leader of Team Skull, Guzma, before the tournament even begins!